A study on the relationship of intention to use fintech the case of digital payment among Malaysian users - Muhamad Shah Ikhwan Shahrum; Muhammad Aidiel Anwar Andri; Muhammad Aiman Mohd Sabri; Muhammad Irfan Mohd Altifaizal (2024)
Fintech and digital payments have become a popular and achievable means of funding projects worldwide. The purpose of this study is to identify the relationship between trust, perceived security, perceived usefulness, and perceived privacy risk and Malaysian users' intention to use digital payments. The relationships of the study were design based on the Technology Acceptance Model (TAM). 400 sample from Malaysian users was collected. By using correlation analysis aid by SPSS, the study found that there is strong positive relationship between trust, perceived security, perceived usefulness, and perceived privacy risk and Malaysian users' intention to use digital payments. The relationship between perceived security and Malaysian users' intention to adopt digital payments was shown to be the strongest among the four hypotheses examined. A strong level of security is prioritized by Malaysian users to protect sensitive, confidential user data and prevent unauthorized access, identity theft or financial fraud.